Influence of Planting Date on Performance of Cauliflower (Brassica oleracea var. botrytis L.) Varieties at Terai Region of West Bengal, India - Islam, S.; Datta, S.; Chatterjee, Ranjit (International Journal of Bio-resource and Stress Management, 2023)
An experiment was undertaken to find out the most suitable time for planting of mid late season cauliflower and to identify the best performing variety/varieties under terai zone of West Bengal. The experiment was laid out in split plot design with three replications. Sub plot consists of five cauliflower varieties viz. Girija, White Excell, Remi, Pushpa and White Marvel and main plot covered three planting dates viz. 15th November, 30th November and 15th December. The pooled results indicated that duration for curd initiation as well as days to curd maturity differ significantly for different varieties as well as different planting dates. Significantly highest curding percentage (75.67%) was observed from 2nd planting date (30th November) whereas among the varieties, Remi gave significantly highest curding percentage (83.97%). The highest net curd weight (620.67 g) was produced by the 15th November planting where White Excell recorded highest net curd weight (820.22 g). Maximum curd yield was recorded by White Excell (26.39 t ha-1) followed by Remi (16.13 t ha-1) and Girija (15.06 t ha-1). White Excell also performed best in all the planting date, whereas Remi performed best in 30th November planting date. The vitamin-A content and ascorbic acid content of cauliflower curd did not differ with the changes of planting dates. Considering the yield and quality parameters it may be concluded that first planting date (15th November) was most suitable for cultivation of the cauliflower varieties viz. Girija, White Excell, Remi, Pushpa and White Marvel except Remi.